Geoenvironmental Assessment of Microplastics: Impacts on Human Health and Marine Ecosystems - Samputri, Salma; Maru, Rosmini; Nasrul, Nasrul; Islami, Andi Widia Anugrah; Nahdawati, Nahdawati; Arfandi, Arfandi (LaGeografia, 2025)
Microplastics have become a significant pollutant that threatens marine ecosystems and human health. Exposure can occur through various pathways, including the consumption of contaminated seafood, drinking water, and airborne particles, all of which may trigger immune disturbances, inflammation, and other toxic effects. This literature review aims to analyze the impact of microplastics on marine ecosystems and human health. Data were collected from Google Scholar and ScienceDirect using keywords related to microplastics, focusing on international publications published between 2019 and 2025. A total of seven relevant articles were reviewed. The findings show that microplastics have contaminated seawater, sediments, and coral reefs, with dominant polymers such as polypropylene (PP) and polyester (PES). The primary sources of microplastics originate from anthropogenic activities, including industrial waste, tourism, and maritime transportation. Impacts on marine ecosystems include physiological disturbances in organisms, reduced reproductive capacity, and increased mortality rates among marine life. Coral reefs also experience declining health due to disrupted photosynthesis of zooxanthellae. In humans, microplastic exposure may affect the digestive, respiratory, and reproductive systems and may lead to chronic inflammation and increased cancer risk. Nano-sized particles from plastic containers can also stimulate immune responses.